Aplicación de mundos virtuales en 3D para la modalidad abierta de la Universidad Técnica Particular de Loja - Juca Aulestia, José Marcelo (2014)
In this paper the implementation of a virtual world that allows enhancing student learning is done, so we designed and built the World UTPL 3D, providing the following infrastructure: classrooms, videoconferencing, debates and legal room duly furnished with the help of OpenSimulador tool, which lets you design virtual environments, with the main feature immersion and communication, emotions and creating meaningful learning as if in real life; also has been used as tools Sloodle has allowed integrating the activities of Virtual Learning Environment and Virtual World; also, the Imprudence viewer that will allow the development of people through avatars. To implement the virtual world, the academic component of Labour Law Law students are selected, creating legal objects (general, history, labor code, criminal code, civil code) allowing recreate a legal environment, considering the doctrine the proper execution of the practice, having a courtroom.